Peculiarities of the modeling of decision-making processes in the field of personal finance - V.V. Didkivskyi; D.S. Antoniuk (Технічна інженерія)
In the conditions of constant technological and economic dynamics of the modern world, managing personal finances becomes an extremely important component of financial stability and well-being for individual consumers. People are exposed to the variety of financial instruments and investment opportunities, which require effective financial management to achieve the financial goals. The article explores the peculiarities of the modeling of decision-making processes in the field of personal finance, focusing on individual characteristics of risk perception. In particular, the article uses prospect theory to analyze decision-making processes in personal finance. This approach allows us to investigate how individual risk perception influences the choice of financial instruments and investment strategies. The results of the analysis demonstrate that attitudes towards risk can determine the choice between risky and stable investments. Noted the possibility of using the approach in the development of algorithmic base and software for modeling decision-making processes in personal finance, that opening up prospects for further development of educational tools aimed at increasing financial literacy.